NUTRITIONAL VALUE OF MORINGA OLEIFERA LEAVES FROM SENEGAL - Juliani, H. R.; Fonseca, Y.; Diatta, M.; Diouf, B.; Simon, J. E. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
Moringa (Moringa oleifera, Moringaceae) is a tropical plant that grows in a wide range of environmental conditions, ranging from sub-tropical dry to moist, through very dry tropical conditions to moist forest zones. Traditionally, moringa leaves and young pods are used as vegetables to aid digestion and to stimulate appetite, to treat inflammatory swellings, externally as counter- irritants. In children is also used to treat fever, bronchitis and headache. The information on moringa is limited on the nutritional value of moringa grown and collected in many African countries. The objective of this research project was to asses the nutritional value of M. oleifera leaves grown and collected in Senegal (Massar, Niaye area). Percentage of moisture, ashes, cleanliness, total proteins, phenols, antioxidants and elemental analysis were performed on dry leaves. Moringa leaves showed low moisture content, lower percentage of total phenols (3-4%), high content of proteins (13-14%) and total minerals (11-13%). The leaves were also high in calcium (2.9-3%), potassium (1%) and iron (50-80mg/100g dry leaves). M. oleifera leaves can be a rich source of nutrients and a good nutritional supplemental to undernourished and malnourished populations particularly those vulnerable sectors such as children, pregnant and lactating women and the elderly. According to the elemental composition, total minerals, and antioxidant phenols Moringa can be an affordable avenue to improve health and nutrition in sub-Saharan countries. Given the ease in growing this tree, the plants adaptability to survive and grow on poor soils under harsh conditions, the introduction of this tree into family gardens, yards and communities would help provide an affordable nutritional food. Current work is now focused on the vitamin and specific polyphenol contents of the leaves.